Towards an integrated understanding of Paleoproterozoic (ca 2.1 to 1.70 Ga) magmatism of the Southern Amazon Craton: tracking crustal evolution and magmatic fertility at Columbia Margin - Martins, José Eduardo Zimmermann da Silva (2023)
The Paleoproterozoic magmatism of the Southern Amazon Craton (ca. 2.1 to 1.7 Ga) produced important gold and base metals mineralization that are partially comprised within the Tapajós and Juruena Mineral Provinces. These accretionary terranes positioned to the west of Archean-Paleoproterozoic basement comprises extensive predominantly undeformed and unmetamorphosed plutonic and volcanic calk-alkaline to alkaline rocks. The understanding of the tectonic setting in which such extensive magmatism took place has been developing and debated in the last decades, so do the understanding and classification of associated metallogenic systems (orogenic gold, IRGD, porphyry-epithermal etc.). More recently the region has been on focus of an exploration rush after the discovery of a typical Cu-Mo porphyry system at the JMP. Nevertheless, the potential for porphyry-epithermal deposits has been highlighted since the discovery of high-sulfidation epithermal deposits at TMP in the 1990s. Therefore, the full mineral potential of these provinces has not been completely accessed yet. Inherent characteristics of the region, a wide tropical forest cover with hard access, and the lack of integrated and comprehensive works has impeded the elaboration of a reliable evolutional history and mineral exploration criteria. In this work we performed comprehensive data compilation and data-driven assessments to unwrap the crustal and magmatic evolution in the accretionary belts of the Southern Amazon Craton and resulting fertility for magmatic-hydrothermal mineral deposits. The compilation work allowed to build a robust and unprecedented geochronological, isotopic and lithogeochemical database that was assessed following stablished scientific and industry methods using modern data analytics tools. Three main magmatic periods were defined and sub-divided in 7 magmatic epochs based on temporal, geochemical and isotopic characteristics: First Magmatic Period: ca. 2070 to 1915 Ma (155 Ma, 3 epochs); Second Magmatic Period: ca. 1915 to 1830 Ma (85 Ma, 2 epochs), and Third Magmatic Period: ca. 1830-1730 (100 Ma, 2 epochs). The First and Second Periods represent fully developed continental magmatic arcs that initiated with subduction-related extended calc-alkaline magmatism that transition to late- and post-tectonic settings when A-type evolved rocks were produced. The Third Period initiated as a calk-alkaline magmatic arc that quickly shifted to a back-arc setting also with voluminous production of A-type rocks. These arcs developed as results of a protracted accretionary orogeny installed over Archean/Paleoproterozoic crust in the context of Columbia Supercontinent assembling, being part of the Great Paleoproterozoic Accretionary Orogen. The variations of environment and petrogenesis identified are strongly suggestive of changes in the tectonic regime caused by variations of the angle of subducting plate, alternating periods of slab-rollback and extension, and periods of flat subduction and compression disclosed by Nd isotopic data. The fertility assessment performed demonstrated that the water content of magmatism constrained by Sr/Y and related ratios varies accordingly to the composition and environment, so do the fertility conditions. High Sr/Y, oxidized, and hydrous rocks are common during the periods of subduction-related calc-alkaline magmatism and are endowed for the formation of typical Cu-Au-Mo porphyries and high sulfidation epithermals systems. Low Sr/Y, A-type anhydrous rocks dominates in the post-subduction and back-arc tectonic settings and are endowed with potential for Au-enriched porphyries and alkalic epithermal systems. Therefore, the results obtained in this work define a better understanding of crustal-magmatic evolution for the region and the associated metallogenetic potential, enabling better criteria for mineral exploration and academic research. Also, it is a significant portraying of one of the biggest and better-preserved branches of the Great Paleoproterozoic Accretionary Orogen and on the tectonics that operated during the assembling of Columbia Supercontinent.